2004
DOI: 10.1029/2004gl020974
|View full text |Cite
|
Sign up to set email alerts
|

Divergent pathways of cyclonic and anti‐cyclonic ocean eddies

Abstract: [1] Satellite altimetry is used to study the propagation pathways of warm and cold ocean eddies in different ocean basins. We consider eddies that have a life span longer than 3 months, and we present three regional studies: in the southeast Indian, the southeast Atlantic, and the northeast Pacific Oceans. The case studies show that simple theories for vortex propagation on a b-plane work in regions where energetic eddies propagate though a weak background flow. Under these conditions, anticyclonic/cyclonic ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
187
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(226 citation statements)
references
References 19 publications
35
187
0
Order By: Relevance
“…The pattern of the first rotated EOF for sea level is clearly very similar to the skewness map presented by Thompson and Demirov (2006). Major eastward currents are delineated by the boundary 5 6 between large positive and large negative values, and preferred paths of eddies, such as in the Alaskan Stream along the Aleutian island chain at the northern boundary of the Pacific (Ueno et al, 2009), and southwest of Australia (Morrow et al, 2004) also stand out. The tropical Pacific is also prominent.…”
Section: Spatial Variations Of the Pdfssupporting
confidence: 60%
“…The pattern of the first rotated EOF for sea level is clearly very similar to the skewness map presented by Thompson and Demirov (2006). Major eastward currents are delineated by the boundary 5 6 between large positive and large negative values, and preferred paths of eddies, such as in the Alaskan Stream along the Aleutian island chain at the northern boundary of the Pacific (Ueno et al, 2009), and southwest of Australia (Morrow et al, 2004) also stand out. The tropical Pacific is also prominent.…”
Section: Spatial Variations Of the Pdfssupporting
confidence: 60%
“…In the eastern and central SCS, mesoscale signals mainly show the westward propagation velocities, which are widely observed in the world oceans and attributed to the influence of baroclinic Rossby waves (Morrow et al, 2004;Chelton et al, 2007). Thus the eddy energy generated west of the Luzon Island will transfer westward, resulting in weak local MV.…”
Section: Discussionmentioning
confidence: 98%
“…Morrow et al (2004) Mediterranean water eddies (meddies) that translate equatorward with some nearby cyclones translating poleward (Richardson et al, 2000). In the western Indian Ocean, de Ruijter et al (2005) found that anticyclones and cyclones form off the southern tip of Madagascar and tend to disperse westward as observed in the Cape Basin.…”
Section: Discussion Of Eddy Translationmentioning
confidence: 99%
“…They appear to enter the Agulhas and translate downstream possibly triggering the shedding of Agulhas rings and cyclones. The different meridional translation direction of the eddies is primarily due to the β effect (Cushman-Roisin, 1994; Morrow et al, 2004). Eddies can also be advected by the background flow field as in the case of Agulhas rings, and eddies can interact with and be advected by other nearby eddies.…”
Section: Discussion Of Eddy Translationmentioning
confidence: 99%
See 1 more Smart Citation